A ascensão da extrema direita no Brasil: uma análise preliminar dos rebatimentos do avanço do neofascismo nas plataformas on-line para a agenda política feminista e LGBTQIAPN+ - Almeida, Vanessa Renata de (2024)
The present study has the objective to study the gender and sexuality content posted by Jair Bolsonaro on online platforms during the presidential election in 2018, identifying neofascism traits in his speech, and understand if his position on the subject guided the public policies aimed at the LGBTQIAPN+ community during his government in Brazil. To this end, we carried out a qualitative documentary and bibliographic research, selecting the ten posts with the most impact on Jair Bolsonaro's Facebook page during his Presidential campaign. Netvizz software was used to extract the Jair Bolsonaro posts and related data from Facebook. Among the results, caught our attention the importance of religious fundamentalism in Bolsonaro's worldview, the strategic use of gender and sexuality comprehension - through the triggering of moral panics - to promote his election, and the importance of social media in the political field in the last years. We also found elements that point to an unprecedented regression in the policies related to gender and sexuality during Jair Bolsonaro's government. This process is part of a broader picture of the neofascism advance across the world in the context of the decline of capitalism